Knowledge, attitudes, and practices of liver cirrhosis patients regarding dietary nutrition - Feng, Yu; Li, Yuqian; Wu, Pengyan; Qian, Xiaoxiao; Zhang, Baofang; Li, Futang (Frontiers in Nutrition, 2026)
ObjectiveThis study aimed to assess the knowledge, attitudes, and practices (KAP) related to dietary nutrition among patients with liver cirrhosis.MethodsA cross-sectional survey was conducted at July 2025 at The Affiliated Hospital of Guizhou Medical University. Participants were patients clinically diagnosed with liver cirrhosis. Data were collected through a structured questionnaire that included items on demographic information, alongside nutritional knowledge, attitudes toward dietary management, and self-reported dietary behaviors.ResultsA total of 450 valid responses were obtained, yielding a response rate of 97.19%. Among the respondents, 318 (70.7%) were male, 233 (51.8%) had a body mass index (BMI) within the normal range, and 127 (28.2%) had been living with cirrhosis for more than 3 years. The knowledge, attitude, and practice scores were 10.96 ± 3.12 (possible range: 0–26), 21.94 ± 2.94 (possible range: 8–40), and 26.52 ± 4.85 (possible range: 8–40), respectively. The structural equation modeling (SEM) showed that knowledge had direct effects on attitude (β = 0.630, p < 0.001) and practice (β = 1.173, p < 0.001). However, neither the direct effect of attitude on practice nor the indirect effect of knowledge on practice was significant.ConclusionIndividuals diagnosed with liver cirrhosis demonstrated limited knowledge, suboptimal attitudes, and insufficient dietary practices related to nutrition. Given these findings, targeted nutritional education should be integrated into routine clinical care to support behavior change and improve dietary self-management in this population.